2008
DOI: 10.1158/0008-5472.can-07-3217
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor–Mediated Decrease in Plasma Soluble Vascular Endothelial Growth Factor Receptor-2 Levels as a Surrogate Biomarker for Tumor Growth

Abstract: Vascular endothelial growth factor

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
89
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 42 publications
9
89
2
Order By: Relevance
“…This result is in accordance to other recent studies, which reported on an antiangiogenic function of sVEGFR-2. 14,15,68,69 These studies demonstrated an inhibition of cell proliferation due to the interaction of VEGF with sVEGFR-2. Corresponding to these studies and regarding to the role of sVEGFR-2, our results corroborate the assumption that sVEGFR-2 functions as an antiangiogenic factor.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…This result is in accordance to other recent studies, which reported on an antiangiogenic function of sVEGFR-2. 14,15,68,69 These studies demonstrated an inhibition of cell proliferation due to the interaction of VEGF with sVEGFR-2. Corresponding to these studies and regarding to the role of sVEGFR-2, our results corroborate the assumption that sVEGFR-2 functions as an antiangiogenic factor.…”
mentioning
confidence: 91%
“…Therefore, a modification of the VEGF effect on prostate tumor growth by sVEGFR-2 is supposable. 14 In addition, recent studies characterized sVEGFR-2 as an endogenous inhibitor of lymphangiogenesis. 15 Recently, we observed that sVEGFR-2 secreted by HPEC binds to VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…The low serum sVEGFR-2 concentrations in these disorders could be explained by the VEGF-induced downregulation of VEGFR-2 receptors as serum-free VEGF concentrations in PE are higher than those in normal pregnancy. Ebos et al (2008) 31 also showed that VEGF-mediated VEGFR-2 downregulation from the cell surface, leads to reduced sVEGFR-2 levels in conditioned media from endothelial cells of tumor, showing that the expression level of VEGFR-2 and its soluble form is linked together. Hence, our results also support that sVEGFR-2 levels reduction may be induced by VEGF-mediated receptor downregulation in hypertensive disorders and suggest that sVEGFR-2 may serve as an indicator of VEGFinduced VEGFR-2 receptor downregulation.…”
mentioning
confidence: 99%
“…[22][23][24] Although both full-length receptors compose an extracellular domain containing sevenimmunoglobulin-like loops, a transmembrane domain, and an intracellular catalytic tyrosine kinase domain, sVEGFR-1 is the product of an alternatively spliced messenger RNA (mRNA) composed of only the extracellular domains. In contrast to sVEGFR-1, very little is known about sVEGFR-2.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Similarly, increased levels of VEGF and reduced levels of sVEGFR-2 have been shown with the use of inhibitors of cellular VEGF receptor tyrosine kinases VEGF RTKs, including sunitinib, 30 axitinib, 31 and telatinib, 32 suggesting a receptor downregulation-mediated increase in sVEGFR-2. Together with in vitro studies in which VEGFinduced endocytosis of VEGFR-2, resulting in lower levels of sVEGFR-2, 22 it seems possible that sVEGFR-2 levels in the plasma of filaria-infected individuals might influence levels of circulating VEGFs in filarial infections. Alternatively, it is possible that sVEGFR-2, like other soluble receptors such as sVEGFR-1, 33 can bind and sequester VEGF in vivo , thereby influencing the binding and activation of the VEGFRs.…”
Section: Discussionmentioning
confidence: 99%